2004
DOI: 10.2298/sos0402087b
|View full text |Cite
|
Sign up to set email alerts
|

Liquid phase sintering of dense and porous glass-ceramics from coal fly-ash and waste glass

Abstract: Glass-ceramics were produced utilizing fly-ash from coal power stations and waste glass of TV monitors, windows and flask glass. The powder technology route was employed. The mixture of 50% fly ash and 50% waste TV glass increases the bending strength from 12±1 to 56±4 MPa and E-modulus from 6±1 to 26±3 GPa. Using polyurethane foam and C-fibers as pore creators porosity of 70±4 and 55±5 %, respectively, can be obtained-modulus and bending strength of the porous systems obtained by polyurethane foam and C-fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…It is very important to convert industrial wastes into pyroxene glass-ceramics because these glass-ceramics are promising materials to be used in construction industry for facing materials due to its high mechanical and chemical properties and low manufacturing cost. 77) Bossert et al 78) fabricated glass-ceramics using fly-ash from coal power stations and waste glass of TV monitors, windows and flask glass. They improved bending strength from 12 to 56 MPa and E-modulus from 6 to 26 GPa at 50% waste TV glass and 50% fly ash mixture.…”
Section: Recycle and Reuse Of Materialsmentioning
confidence: 99%
“…It is very important to convert industrial wastes into pyroxene glass-ceramics because these glass-ceramics are promising materials to be used in construction industry for facing materials due to its high mechanical and chemical properties and low manufacturing cost. 77) Bossert et al 78) fabricated glass-ceramics using fly-ash from coal power stations and waste glass of TV monitors, windows and flask glass. They improved bending strength from 12 to 56 MPa and E-modulus from 6 to 26 GPa at 50% waste TV glass and 50% fly ash mixture.…”
Section: Recycle and Reuse Of Materialsmentioning
confidence: 99%
“…The first is controlled crystallization, meaning that melted fly ash is exposed to the one or two steps of the heat treatment for crystallization followed by nucleation and crystal growth [12][13][14][15]. The second technique developed for glass-ceramics production involves sintering of the fly ash with or without any additives [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The similarity in the chemical composition of the fl y ash and clay make the fl y ash a possible substitute for clay consumption. By using different materials as pore creators there are many procedures that are usually employed to make porous ceramics products (Wu, Boccaccini, Lee, Kershaw and Rawlings, 2006;Bossert et al, 2004;Mangutova, Fidancevska, Milosevski and Bossert, 2004). Wang et al (2008) reported for developing lightweight aggregate from fl y ash and dry sewage sludge.…”
Section: Introductionmentioning
confidence: 99%